Nanoscale analysis of the influence of pre-oxidation on oxide formation and wetting behavior of hot-dip galvanized high strength steel. (April 2015) - Arndt, M.; Duchoslav, J.; Steinberger, R.; Hesser, G.; Commenda, C.; Samek, L.; Arenholz, E.; Stifter, D.
Highlights: Pre-oxidized hot-dip galvanized advanced high strength steel was examined. The interface was analyzed in detail via high energy resolution Auger spectra. Evidence for an aluminothermic reduction of the Mn oxide was found. A new model for galvanizing high manganese steel was developed. Abstract: Hot-dip galvanized (HDG) 2nd generation advanced high strength steel (AHSS), nano-TWIP (twinning induced plasticity) with 15.8 wt.% Mn, 0.79 wt.% C, was analyzed at the interface between steel and zinc by scanning Auger electron microscopy (AES) in order to confirm and improve an existing model of additional pre-oxidation treatment before annealing and immersion into the hot zinc bath. Furthermore these steel samples were fractured in the analysis chamber of the AES and analyzed without breaking vacuum. In these measurements the results of an aluminothermic reduction of the manganese and iron surface oxides on the steel could be confirmed by AES.